نغمہ زارِ حفیظ - بصیرہ عنبرین (Tabeer e Nau, 2026)
This article presents a sensitive and insightful appreciation of Hafeez Jalandhari and his celebrated poetic collection Naghma Zar. The study highlights Hafeez's unique contribution to Urdu lyrical poetry, particularly his ability to transform the traditional geet into a vibrant expression of human emotions, cultural memory, and musical beauty. His poetry reflects the colours of everyday life, the charm of changing seasons, the spirit of festivals, and the emotional warmth of love and patriotism. Poems such as "Barsaat", "Krishan Bansri", and "Preet Ka Geet" reveal his deep attachment to local culture and his remarkable talent for blending melody with feeling. The article also discusses the admiration expressed by critics like Josh Malihabadi and Firaq Gorakhpuri, who viewed Hafeez's poetry as emotionally rich, melodious, and artistically original. The essay further explains that the enduring beauty of Naghma Zar lies in its simplicity, musical flow, and heartfelt expression. Hafeez Jalandhari combined Indian folk imagery and local linguistic flavour with the elegance of Persian and Arabic poetic traditions, creating a poetic voice that feels both refined and deeply human. His verses do not merely describe scenes; they awaken emotions, memories, and a sense of cultural belonging. Through rhythm, repetition, vivid imagery, and lyrical softness, Hafeez gave Urdu poetry a fresh musical dimension that continues to resonate with readers. The article concludes that Naghma Zar occupies a distinguished place in modern Urdu literature because it celebrates beauty, humanity, and emotional sincerity while preserving the cultural and artistic spirit of its age.